Theoretical-Methodological Problems of Service Sector Development - Urunbayeva Yulduz Pirnazarovna; Fayzullayeva Sabrina Uyg‘un qizi (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article emphasizes that the development of the services sector is a key factor in the socio-economic development of the country.